Empowering diverse voices: Teaching costume design in the MENA region - Andrea Forde
This essay explores the ways in which the BFA production arts course, at the Sharjah Performing Arts Academy (SPAA), provided an opportunity for students to challenge cultural stereotypes in a design project presented at the Prague Quadrennial (PQ) in 2023. The project brief asked students to reimagine superhero costume design tropes using a range of Middle East and North African (MENA) cultural symbols and motifs. The costume design component of the design realization course at SPAA is the only one of its kind in the MENA region, placing it in a unique cultural context. This distinct positioning allows students to engage deeply with their cultural heritage, while also pushing the boundaries of contemporary and traditional design. The project’s emphasis on integrating MENA cultural elements into superhero costumes aimed to both celebrate and reinterpret these symbols, offering fresh design perspectives and the opportunity to challenge stereotypical representations. By leveraging their individual cultural backgrounds, students were able to produce designs that were innovative and culturally resonant, showcasing the rich tapestry of MENA heritage on an international stage. Through this initiative, SPAA’s programme not only provided a platform for creative expression but also encouraged critical thinking about costume design’s role in cultural identity and representation for both SPAA students and PQ’s international audience.